Seeing double after sinus surgery - H Ranjini; R Neena; Marian Pauly (Kerala Journal of Ophthalmology)
A 40-year-old gentleman came to us with protrusion, redness, and mild pain in right eye immediately after undergoing functional endoscopic sinus surgery. He complained of constant horizontal diplopia. He had large angle right eye exotropia (modified krimsy = 50 PD exotropia) with -4 limitation of adduction with palpebral fissure widening on adduction, features suggestive of transection/avulsion of right medial rectus (MR). Magnetic resonance imaging of orbits confirmed the clinical findings. MR exploration was done. Intraoperatively, MR was transected about 15mm from the insertion. A challenging attempt was made to bring back the piecemeal posterior edge and reattach to the anterior edge with hang back sutures. Injection Botulinum toxin was given to right lateral rectus. Diplopia persisted after primary repair and patient was given prism glasses. Eventually a vertical rectus muscle transposition to MR with foster augmentation was done along with injection Botulinum toxin to lateral rectus. Four years postoperatively, patient maintained good alignment in primary position and is diplopia-free in straight gaze for distance and near. Timely exploration with staged squint correction provided acceptable functional outcome to our patient.